The Effect of Organizational Culture on Technology Transfers and Company Performance - Rival Cahya Setiawan; Evi Susanti; Tantri Yanuar R Syah (Journal of Multidisciplinary Academic, 2019)
This study aims to examine the effect of organizational culture on technology transfer and company performance. This study will raise the relationship between technology transfer and company performance as a literature gap. The population used in this study is the largest motor vehicle automotive parts manufacturing by Group Company in Indonesia with a joint venture company with a total of 33 companies. The sample technique used is saturated sampling using 66 production managers as respondents from each company. The research method and data analysis in this study is use a Mix Method with Sequential Explanatory design. To validate the significant level and interrelationships between variables, we use Partial List Square (PLS) method and Smart PLS 3.0. The results shows that the application of organizational culture had a positive and significant effect on technology transfer and company performance. This study also refutes previous research which states that technology transfer has no effect on company performance. In addition it was found that technology transfer has a role as mediation between organizational culture and company performance, so the better the organizational culture of the company, the application of technology transfer will increase so that the company's performance will be better.